Barbell kinetics and kinematics of the clean in female national weightlifters: a comparison between medallists and non-medallists - Chavda, S.; Yao, X.; Harcoff, J.; Martin, S.; Bishop, C.; Turner, A. (The Journal of Strength and Conditioning Research, 2021)
Purpose: The purpose of this study was to investigate kinetic and kinematic bar characteristics differentiating female medallist and non-medallists in the clean, during a national weightlifting competition. Methods: The heaviest successful clean attempts from 30 female weightlifters at the 2019 English Senior Weightlifting Championships were examined. Athletes were split into 2 groups based on their rank: medallists (n = 15) and non-medallists (n = 15). All lifts were recorded using a high-speed camera (165.04 fps) (Quintic Consultancy Ltd, United Kingdom) situated on the left side of the competition platform. All videos were automatically digitised in biomechanical software (Quintic version 31, Quintic Consultancy Ltd, United Kingdom) utilising a reflective marker placed on the left side of the bar. Raw positional, velocity and acceleration data were filtered using a 10 Hz Butterworth filter. All data was extracted and analysed in a custom excel spreadsheet. Work and power of the bar was calculated utilising the methods outlined by Garhammer (1993). 27 variables were extracted for analysis relating to: load, displacement, velocity, acceleration, work and power. A one-way ANCOVA was conducted to compare mean loads lifted by the groups controlling for bodyweight. An independent samples t-test was conducted to compare mean differences of bar variables between groups. Practical differences were identified using Hedges' g effect size (ES), with 95% confidence intervals (95% CI). ES descriptors were defined using the guidelines outlined by Cohen (1988). Results: As presented in Table 1, 9 variables were found to have moderate to large significant differences between groups, suggesting that forward acceleration and velocity of the barbell away from the lifter, maybe a discriminatory factor between National medallists and non-medallists. Conclusions: Key findings suggested that non-medallists lifted significantly less than medallists and as a consequence of this they were able to generate a significantly larger magnitudes of vertical velocity on the barbell, allowing for a greater vertical displacement and therefore enabling them to catch the bar at a higher height. The results also highlighted that non- medallists displaced the bar significantly further away from them following contact during the clean. This is likely due to the significantly greater magnitudes of horizontal acceleration and velocity applied on the barbell, suggesting that training in lower achieving national weightlifters should focus on appropriate force application to the bar. Practical Application: Reducing the horizontal acceleration and velocity away from the body during the second pull may aid in the development of reducing the loop during the clean. Furthermore, utilising derivatives focusing on the second pull, such as from the power position and hang may help facilitate the training of appropriate technique and the application of vertical force on to the barbell, whilst concurrently reducing the loop. It should also be acknowledged that as load increases lower vertical displacements will be achieved, therefore athletes should also focus on the speed of the turnover in preparation for the catch.